2014
DOI: 10.1179/1362171814y.0000000208
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of tungsten inert gas welded–brazed Mg/Ti lap joints

Abstract: The tungsten inert gas (TIG) welding-brazing technology using Mg based filler was developed to join AZ31B Mg alloy to TA2 pure Ti in a lap configuration. The results indicate that robust joints can be obtained with welding current in the range of 60-70 A and welding speed of 0?2 m min 21 . The joints were found to be composed of the coarse grained fusion zone accompanied with the precipitated phase of Mg 17 Al 12 , and a distributed Mg-Ti solid solution zone at the interface of Mg/ Ti, indicating that metallur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Lv et al have proposed a novel TIG welding process called keyhole arc weldingbrazing that was used to join Ti-6Al-4V and 5A06 Al. 11 Wan et al have joined aluminised Ti-6Al-4V and 5A06 Al and found that the ability of liquid filler metal to spread on the Ti substrate was significantly enhanced by 1 the presence of an aluminised coating. 12 Cao et al have used low heat input to restrict the formation of Al/Ti IMCs during cold metal transfer welding-brazing.…”
Section: Introductionmentioning
confidence: 97%
“…Lv et al have proposed a novel TIG welding process called keyhole arc weldingbrazing that was used to join Ti-6Al-4V and 5A06 Al. 11 Wan et al have joined aluminised Ti-6Al-4V and 5A06 Al and found that the ability of liquid filler metal to spread on the Ti substrate was significantly enhanced by 1 the presence of an aluminised coating. 12 Cao et al have used low heat input to restrict the formation of Al/Ti IMCs during cold metal transfer welding-brazing.…”
Section: Introductionmentioning
confidence: 97%
“…However, in the process of non-uniform cooling, the coarse grain appeared, accompanied by the precipitated phase of Mg 17 Al 12 in the fusion zone. In addition, the maximum tensile-shear strength of 193.5 N/mm, which represents 82.3% joint efficiency relative to the Mg alloy base metal, was attained [11]. Gao studied dissimilar Ti/Mg alloy butt welding by fibre laser with Mg filler wire-preliminary, observing some flake or a granular mixture of α-Ti, α-Mg and Mg 17 Al 12 in the fusion zone [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fusion welding process is the method used for joining similar metals. However, the application of any fusion welding technique to join dissimilar metals presents additional difficulties, the first one being; the reaction of the two metals at the joint interface can create compounds that may have unfavourable properties [9] [10]. Another limitation to the use of these alloys includes galvanic corrosion due to differences in electrode potential values between the materials.…”
Section: Introductionmentioning
confidence: 99%
“…The method has been shown to promote joining by removing surface oxide and ensuring metal-to-metal contact. Sheng et al [9] created a Ti/Mg lap joint using tungsten inert gas welding [13] [14]. Joint formation and the strength developed in diffusion bonds have been shown to relate to the width of the reaction layer formed at the interface during joining.…”
Section: Introductionmentioning
confidence: 99%